2007
DOI: 10.1007/s11199-007-9227-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Change in Feminist Activism Through Women’s and Gender Studies

Abstract: Predictors of change in feminist activism were studied in a group of 519 women and 143 men enrolled in 48 women's and gender studies (WGS) classes on six college campuses in a large Midwestern urban area. Over the semester-long classes, students increased their feminist activist behaviors and intention to engage in future activism. Although women had greater activist behaviors and intentions than men, increases were similar for women and men across time. African American and Euro American students increased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…In this way, the Activist condition employed a conceptualization used in activism research (Stake, 2007;Szymanski, 2012). After removing the eight participants who indicated that they could not think of a specific White activist, the Activist condition included 37 participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the Activist condition employed a conceptualization used in activism research (Stake, 2007;Szymanski, 2012). After removing the eight participants who indicated that they could not think of a specific White activist, the Activist condition included 37 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Activism is conceived as intentional action designed to promote social and/or political change (Stake, 2007;Szymanski, 2003). Particularly given the intractable, systematic nature of various systems of inequality in many societies, activism can include formal, confrontational forms, such as demonstrations, rallies, boycotts, or letter-writing campaigns (Montgomery & Stewart, 2012;Szymanski, 2004), as well as informal, non-confrontational activism, including mentoring, discussing racial bias with others, or becoming educated about discriminatory situations (Szymanski, 2012).…”
Section: Allies' Similarity To Friends and Activistsmentioning
confidence: 99%
“…Or perhaps the nature of college life offers an insular environment in which students begin to question and adopt new views from those in their family upbringing. A vast amount of research has been conducted on the liberalizing effect of college courses and women's studies classes in particular (e.g., Aronson 2003;Bryant 2003;Stake 2007). Using the life course perspective as a model to understand this dynamic, perhaps it is this intersection between unique individual experiences (e.g., college experiences, gender, peers) and broader societal events (e.g., political climate, women in the news) that contributes to the lack of family influence seen.…”
Section: Family Influencementioning
confidence: 99%
“…Surprisingly, very little research has focused on African American person's engagement in collective responses to oppression. However, research examining the links between sexism and feminist activism has been conducted (cf., Duncan, 1999;Liss, Crawford, & Popp, 2004;Stake, 2007;Szymanski & Owens, 2009;Yoder, Tobias, & Snell, 2011), underscoring the importance of activism as a variable of study. Thus, the purpose of this study was to examine the extent to which African American persons are involved in a range of African American activism activities and to investigate variables that may predict involvement in African American activism.…”
mentioning
confidence: 99%